Online Trading Practices from the Perspective of Fiqh Muamalah (Analysis of Contracts, Gharar, and Khiyar Mechanisms) - Nur Sania Dasopang; Putra Halomoan Hasibuan (Islamic Circle, 2025)
The development of digital technology has transformed conventional buying and selling practices into electronic transactions, giving rise to new issues from the perspective of fiqh Muamalah. This study aims to analyse online buying and selling practices through a trilogy approach to the concepts of Akad, Gharar, and Khiyar. The method used is qualitative, with a library research approach and content analysis of primary and secondary sources. The results of the study show that: First, electronic contracts have fulfilled the pillars and requirements of contracts through the digital transformation of ijab-qabul with the support of DSN-MUI fatwa No. 116/DSN-MUI/IX/2017. Second, the potential for gharar in e-commerce can be mitigated through technologies such as digital reputation systems, escrow, and blockchain. Third, the Khiyar mechanism has been actualised through return features, digital previews, and delivery method selection. This study concludes that sharia e-commerce is not only valid in fiqh, but also strengthens consumer protection when integrated with national regulations. The research recommendations include the development of an integrated sharia and national consumer protection system model to create a fair e-commerce ecosystem.